Impact of Pre-admission Observation Hours on Key Physical Therapist Clinical Education Stakeholders: Qualitative Analysis. Issue 2 (1st June 2022) - Hoang, Thuha; Watkins, Molly; Bayliss, Jamie; Schack-Dugre, Judi; Mitchell, Katy; Mariano, Mira; Greco, Jamie; Colgrove, Yvonne; Wheeler, Emma; Kiyota, Hiroshi; Pientok, Colette; Stephens, Laura; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Inclusion of preadmission observation hours (ObHr) as one component of the admissions process is commonly required in physical therapy education programs. The purpose of this study was to describe the value and impact of ObHr on 4 key stakeholder groups: doctor of physical therapy students, physical therapy clinicians, directors of clinical education, and admissions committee (AC) members. Review of Literature: The number of required and/or recommended ObHr and practice settings varies greatly. No previous study has explored a national dataset of key stakeholders' perspectives on ObHr experiences. Subjects: Four key stakeholder groups were targeted in the study ( N = 4, 471). Methods: Four stakeholder surveys were developed and distributed via email using a snowball sampling technique. Responses to the open-ended questions were analyzed using conventional content analysis for creating codes, categories, and themes within and across groups. Results: Five main themes emerged: 1) ObHr have value in career decision making; 2) students driven by hours, but all stakeholders value variety; 3) use of ObHr for program admissions decisions varies; 4) as the number of hours and settings increase, so do the challenges for students; and 5) there is interest in developing alternative ObHr experiences. Discussion and Conclusion: There was consensus among all stakeholder groups regarding ObHr's value for exploring the profession of physical therapy and helping applicants determine if the profession is a good fit. Respondents highlighted the value of observing in a variety of practice settings. Perspectives differed between AC members and students regarding the impact of ObHr on admissions decision making. Students reported a variety of personal and organizational challenges associated with ObHr completion. Physical therapy programs should reexamine their current ObHr practices and consider alternative methods that support all applicants in their pursuit of a career in physical therapy.